Evaluasi Komunikasi Orang Tua Dan Anak Era Digital Perspektif Kitab Nitisastra - I Putu Sawangga Dhana; I Wayan Dana; I Gusti Ayu Ketut Yuni Masriastri (Fakultas Dharma Duta, 2026)
The digital age and the widespread use of smartphones have greatly changed how families communicate. The habit of ignoring others for a phone, known as phubbing, has lowered the quality of the relationship between parents and children. This literature review examines family communication in the digital era using the values of the Nitisastra. It also reviews how previous studies on this topic were conducted. By analyzing research published between 2016 and 2026, the findings show that smartphone distractions hinder children's mental and emotional development. As a solution, the Nitisastra provides an age-appropriate communication guide to help rebuild emotional bonds in the family. Furthermore, this study finds that previous research relies too much on self-assessments, which can be inaccurate. Therefore, future studies should use more in-depth and varied methods to evaluate family communication.